“AN ANALYSIS OF MADRASAH CURRICULUM DEVELOPMENT IN ELEMENTARY SCHOOL” - Permata, Indah Wahyu (Journal of Research on Language Education, 2024)
The purpose of this research is to provide an explanation of the curriculum creation process, which includes curriculum planning, curriculum implementation, and curriculum evaluation, based on Madrasah Ibtida'iyah Islamiyah Kijang. This kind of research is descriptive qualitative research that is offered with an emphasis on examining how MI Islamiyah Kijang is implementing its current curriculum. According to the study's findings, creating a curriculum for a madrasah school requires many steps: (1) The process of creating a curriculum involves striking a balance between religion and general science disciplines. (2) The Ministry of Religion and the Ministry of Education and Culture work together to implement the curriculum, focusing on religious studies and life skills. The detailed subject matter is prepared for the curriculum. (3) Student attitudes and the attainment of learning objectives are the basis for curriculum evaluation. (4) The "Collaborative Curriculum Model" refers to the process used to construct the madrasah curriculum at MI Islamiyah Kijang.Keywords: Curriculum development, Madrasah, Collaborative curriculum